Analysis of the Relationship between Hamming Distance and the Electromagnetic Information Leakage - Zhang Jiemin; Liu Jinming; Sun Haimeng; Mao Jian (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Electromagnetic information leak as a potential data security risk is more and more serious. Discussing the relationship between compromising emanations and Hamming distance is directed to preventing or reducing the electromagnetic information leakage. The paper presents the model of electromagnetic information leak, then the hierarchical protection strategy based on the model is proposed, that is anti-radiation, anti-intercept and anti-reconstruction. Analyzing the causes of electromagnetic information leak through the touch screen case, the paper describes the electromagnetic radiation intensity is correlated to the transition's Hamming distance. The paper presents the anti-intercept method, which is reducing the Hamming distance of the sensitive data or keep Hamming distance constant in order to reducing or preventing the electromagnetic information leakage. The anti-intercept method is available showed as the touch screen case. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3966